Afghanistan's local war : building local defense forces - Jones, Seth G., 1972- (Rand Corporation monograph series ;, 2010)
Security in Afghanistan has historically required a combination of top-down efforts from the central government and bottom-up efforts from local communities. Since 2001, U.S. and broader international efforts have focused on establishing security solely from the top down through Afghan national security forces and other central government institutions. But local security forces are a critical complement to these efforts, especially in rural areas of the country. The Afghan government and NATO forces need to move quickly to establish a more-effective bottom-up strategy to complement top-down efforts by better leveraging local communities. The Afghan government can work with existing community structures that oppose insurgents to establish village-level policing entities, such as arbakai and chalweshtai, with support from NATO. Effectively leveraging local communities should significantly improve counterinsurgency prospects and can facilitate mobilization of the population against insurgents. This analysis documents lessons about the viability of establishing local security in Afghanistan and addresses concerns about the wisdom of such policies.